War and the Christian conscience where do you stand? - Fahey, Joseph J. (Maryknoll, NY Orbis, 2005)
Contents : Part 1: Conscience : Nicole's conscience; Conscience and what forms it. Part 2: War and conscience in Christian history : Pacificism; Just war; Total war; World community. Part 3: War and your conscience. Includes bibliographical references.
Keywords: War -- religious aspects -- Christianity